Pulmonary inflammation decreases with ultra-protective ventilation in experimental ARDS under VV-ECMO: a positron emission tomography study - Deniel, Guillaume; Dhelft, François; Lancelot, Sophie; Orkisz, Maciej; Roux, Emmanuel; Mouton, William; Benzerdjeb, Nazim; Richard, Jean-Christophe; Bitker, Laurent (Frontiers in Medicine, 2024)
Background: Experimentally, ultra-protective ventilation (UPV, tidal volumes [VT] < 4 ml.kg -1 ) strategies associated with veno-venous extra-corporeal membrane oxygenation (VV-ECMO) are associated with lesser ventilator induced lung injuries (VILI) during acute respiratory distress syndrome (ARDS). But whether these strategies reduce lung inflammation more effectively than protective ventilation (PV) remains unclear. We aimed to demonstrate that a UPV strategy decreases acute lung inflammation, as compared to PV in an experimental swine model of ARDS.Methods: ARDS was induced by tracheal instillation of chlorohydric acid in sedated and paralyzed animals under mechanical ventilation. Animals were randomised to receive either UPV (VT 1 ml/kg , positive end-expiration pressure [PEEP] set to obtain plateau pressure between 20-25 cmH2O and respiratory rate [RR] at 5/min under VV-ECMO) or PV (VT 6 ml/kg , PEEP set to obtain plateau pressure between 28-30 cmH2O and RR at 25/min) during 4h. After 4h, a positron emission tomography with [ 11 C](R)-PK11195 (ligand to TSPO-bearing macrophages) injection was realised, coupled with quantitative computerized tomography (CT). Pharmacokinetic multicompartment models were used to quantify regional [ 11 C](R)-PK11195 lung uptake. [ 11 C](R)-PK11195 lung uptake and CTderived respiratory variables were studied regionally across 8 lung regions distributed along the anteroposterior axis.Results: Five pigs were randomised to each study group. Arterial O2 partial pressure to inspired fraction in O2 were not significantly different between study groups after experimental ARDS induction. Compared to PV animals, UPV animals displayed a significant decrease in the regional non-aerated compartment in the posterior lung levels, in mechanical power and in regional dynamic strain, and no statistical difference in tidal hyperinflation after 4 hours. UPV animals had a significantly lower [ 11 C](R)-PK11195 uptake, compared to PV animals (non-displaceable binding potential 0.35 [IQR, 0.20-0.59] in UPV animals, and 1.01 [IQR, 0.75-1.59] in PV animals, p=0.01). Regional [ 11 C](R)-PK11195 uptake was independently associated with the interaction of regional tidal hyperinflation and regional lung compliance.In an experimental model of ARDS, 4h of UPV strategy significantly decreased lung inflammation, in relation with the control of VT-derived determinants of VILI.